2013
DOI: 10.1039/c2cp43350h
|View full text |Cite
|
Sign up to set email alerts
|

The strain effect on colossal oxygen ionic conductivity in nanoscale zirconia electrolytes: a first-principles-based study

Abstract: Density functional theory calculations and first-principles molecular dynamics (MD) simulations have been performed to examine the strain effect on the colossal oxygen ionic conductivity in selected sandwich structures of zirconia electrolytes. For the KTaO(3)/YSZ/KTaO(3) sandwich structure with 9.7% lattice mismatch, transition state calculations indicate that the strain effect changes the oxygen migration pathways from straight line into zigzag form and reduces the energy barrier by 0.2 eV. On the basis of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
1
16
1
Order By: Relevance
“…Besides, the STO structure is more stable than 7%-strained YSZ at the YSZ/STO interface. They suggested that a lower enhancement of 4× 10 4.6 should be obtained for 7%-strained YSZ at 500 K. Utilizing the same methods with Pennycook et al 58 , another exceedingly large enhancement in the ionic conductivity for YSZ was observed by Li et al 66 But they substituted STO with another perovskite oxide ABO 3 (KTaO 3 and Al 2 O 3 ), constituting sandwich structures ABO 3 /YSZ/ABO 3 . 3b.…”
Section: Enormous Impact Of Lattice Strain On Ionic Migration Energy/mentioning
confidence: 90%
“…Besides, the STO structure is more stable than 7%-strained YSZ at the YSZ/STO interface. They suggested that a lower enhancement of 4× 10 4.6 should be obtained for 7%-strained YSZ at 500 K. Utilizing the same methods with Pennycook et al 58 , another exceedingly large enhancement in the ionic conductivity for YSZ was observed by Li et al 66 But they substituted STO with another perovskite oxide ABO 3 (KTaO 3 and Al 2 O 3 ), constituting sandwich structures ABO 3 /YSZ/ABO 3 . 3b.…”
Section: Enormous Impact Of Lattice Strain On Ionic Migration Energy/mentioning
confidence: 90%
“…In this paper, we report the combined EELS and ADF optical sectioning of thin film heterostructures composed of yttria-stabilized zirconia (Y 2 O 3 ) x (ZrO 2 ) 1−x (YSZ) and SrTiO 3 (STO), a system which has sparked intense debate due to the observation of colossal ionic conductivity at coherent YSZ/STO interfaces [17,18,19,20,21,22,23,24,25,26,27]. Observing a sample with significant islanding, and hence a high level of overall inhomogeneity, we found regions which EELS shows to contain the elements of both YSZ and STO.…”
Section: Introductionmentioning
confidence: 99%
“…Although empirical potentials in such classical MD simulations permit the use of large unit cells and long simulation times, the obtained results are not always reliable compared to those of ab initio calculations. Ab initio MD calculations by Pennycook et al 19 and Li et al 20 indicated the enhanced ionic conductivity at 7-10% tensile strain along the a-and b-axes. Additionally, Li et al took into consideration the interface effect, which can enhance the ionic conductivity to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…However, Li et al concluded that the interface does not produce a prominent increase in the ionic conduction. 20 Generally, their ab initio MD calculations should be more reliable than the classical MD results. However, the feasible unit cell sizes and simulation times have been limited because of the computational cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation